(untitled) (Sound Stage Screen, 2025)
Review–essay of the generative documentary Eno, directed by Gary Hustwit. Brendan Dawes (director of programming), Mary Farbrother (director of photography). Generative software by Anamorph. Screened at Sheffield DocFest on Sunday 16th June 2024.